Notice of RETRACTION: Randomized Open Clinical Trial to Evaluate Netratarpana Efficacy in Elderly Patients with Primary Insomnia (Anidra) - Kulkarni, Satyajit Pandurang; Chugule, Pritam; Kulkarni, Pallavi Satyajit (Sciences of Pharmacy, 2025)
This article has been retracted due to non-compliance with the journal’s Clinical Trial Registration Policy. The study reported a clinical trial that was not registered in a WHO-recognized public registry, as required by international standards (ICMJE, WHO, COPE). Although the author sought retrospective registration, no confirmation was provided within the required timeframe. The editors apologize for not identifying this issue before publication.